2021
DOI: 10.1016/j.xfre.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Traits of patients seen via telemedicine versus in person for new-patient visits in a fertility practice

Abstract: Objective: To assess the differences in demographics, the likelihood of receiving treatment, and the clinical outcomes between new patients seen via telemedicine and those seen in person in an academic fertility practice. Design: Retrospective cohort study. Setting: University-based fertility clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…As part of the ASRM strategic plan for 2014-2019, a focus was on "access to care" because an estimated 39.6% of the US population has limited ART access [14,15]. Telehealth can facilitate access to care [8]; however, with this survey, we demonstrated an arguably more important point: patients are satisfied with telehealth and preferred it in most cases. Currently 30 states have parity laws which ensure health insurance companies have equivalent reimbursement for in-person and telehealth services.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As part of the ASRM strategic plan for 2014-2019, a focus was on "access to care" because an estimated 39.6% of the US population has limited ART access [14,15]. Telehealth can facilitate access to care [8]; however, with this survey, we demonstrated an arguably more important point: patients are satisfied with telehealth and preferred it in most cases. Currently 30 states have parity laws which ensure health insurance companies have equivalent reimbursement for in-person and telehealth services.…”
Section: Discussionmentioning
confidence: 79%
“…The ADI can help to represent socioeconomic status (SES) depending on geographic location with a higher number (from 0 to 100) indicating higher disadvantage. The ADI has been previously used to compare trait differences in patients undergoing telehealth versus in person visits in a fertility practice [8].…”
Section: Introductionmentioning
confidence: 99%
“…This first face-to-face-visit step is also important for training, as patients and/or caregivers must be capable to use the telemedicine system. This approach was successfully adopted to design care models in populations with various medical issues [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the backlog might be due to the increased social distancing and the changes that fertility clinics had had to make to be able to cope with staff illness (Bhattacharya et al, 2021). The addition of telehealth to a protocol has been suggested to help patients by reducing the emotional stress of delays while also maintaining fertility care (Alexander et al, 2021;Berg et al, 2020;Dilday et al, 2021;Gemmell et al, 2020;Karavani et al, 2021). Additionally, by using a telehealth service prior to in-clinic appointments doctors would have a better understanding of patient prognosis and give them the ability to order patients by priority (Hernández et al, 2020).…”
Section: Discussionmentioning
confidence: 99%